2022
DOI: 10.1002/dc.24930
|View full text |Cite
|
Sign up to set email alerts
|

Bile cytology diagnosis in challenging cases: Validation of diagnostic bile cytology criteria and extensive study for immunocytochemical markers

Abstract: Background Bile cytology is useful in diagnosing biliary tract lesions, albeit often challenging due to equivocal findings. To achieve better diagnoses for clinical decisions, we conducted cytomorphological and immunocytochemical studies of bile cytology cases. Materials and methods We re‐evaluated 40 bile cytology cases with initial equivocal diagnoses, taken from the cytology records of Jichi Medical University Hospital, including 1778 bile cytology specimens. First, we assessed the cases by the diagnostic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Therefore, we also believe that it is necessary to construct a scoring system that focuses on differentiating between WDAC and benign cells in the future. Moreover, Sano et al 9 also reported that combined immunocytochemistry and morphological evaluation might facilitate a more accurate diagnosis. Therefore, further improvements in accuracy can be achieved by combining the scoring system with immunostaining or fluorescent in situ hybridization (FISH).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we also believe that it is necessary to construct a scoring system that focuses on differentiating between WDAC and benign cells in the future. Moreover, Sano et al 9 also reported that combined immunocytochemistry and morphological evaluation might facilitate a more accurate diagnosis. Therefore, further improvements in accuracy can be achieved by combining the scoring system with immunostaining or fluorescent in situ hybridization (FISH).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding WDAC determination, a factor contributing to the compromised diagnostic accuracy of bile cytology, differentiation of malignant cells is difficult owing to weak atypia, which often resembles benign cells. 9,16 Our SSBC was designed to improve the accuracy of differentiating between malignant and benign cells, including WDAC cells, while also reducing the number of indeterminate cases.…”
Section: Scoring System First Scoring Evaluationmentioning
confidence: 99%
See 3 more Smart Citations